Tantangan dalam koordinasi jaminan kesehatan Aceh - Saputra, Edy (Jurnal Kependudukan Indonesia, 2013)
Aceh's Health Insurance (JKA) is a health insurance with the concept of universal health insurance and is organized through social insurance mechanisms. JKA is applied for the whole population of Aceh in order to overcome the constrains of cost barriers for the population that still require an improvement as a result of a 30 years armed conflict. In practice, JKA still faces various problems both in the preparation period as well as the implementation of the programs. The biggest problem is coordinating various elements of the organizations that are involved in the implementation of the JKA, these organizational elements include; the Government of Aceh, the academics, PT. Askes, and the organizations and health professionals as well as the civil society. This paper aims to analyze the challenges of coordinating the implementation of JKA through the approach of the Focus Group Discussions method and interviews that were conducted in 2012. The results of the study showed that the problems that were faced in coordinating JKA, among others; lack of understanding of the JKA's Grand Design, the obscurity of the working relationships between each of the elements related to the organization, the differences in the perception of interpreting and implementing the guidelines, and the fact that there was no coordination of standards and technical guidelines of the JKA. Related to these problems, the authors recommend, among others; to strengthen the understanding of the grand design of the programs related to the various elements of the organization, to optimize the socialization and dissemination of guidelines to the related organizations, to formulate working relationships between organizations, to arrange and disseminate the standard operating procedures for the coordination between the JKA programs, and to conduct Tripartit meeting per - quarter yearly.